Phenomenological Study of the Use of Discord Application as a Medium of Da’wah Communication to the Salam Talk Community - Fita Fathurokhmah; Andini Patria Damayanti (Ittishol: Jurnal Komunikasi dan Dakwah, 2023)
Da'wah, that is happening today, is no longer centered on the pulpit. One of the phenomena carried out in the newest application is Discord, which game players widely use for preaching in a modern way through an existing community, namely "Salam Talk." This research was used to answer questions about the occurrence of the Difusi phenomenon of using the Discord application in the "Salam Talk" community in preaching and the supporting factors for the occurrence of the phenomenon in the "Salam Talk" community. The theory used is Alfred Schutz's phenomenological theory, which specializes in the experiences of each member with a concentration on problems arising from textual interpretation. The research method used is Merleau-Ponty's phenomenology, describing phenomena, context, and situation as part of the approach. The phenomenon in this study is the experience of using Discord as a da'wah medium in the "Salam Talk" community. The findings of this study obtain results that are present in the form of ease in learning about Islam. With sensory experiences, such as wise experiences that involve interaction, emotional experiences include affection for the community and reflective experiences when one understands phenomenal thoughts. These social experiences involve interaction between members and religious experiences that make a person feel more able to deepen his religion while experiencing movement. The phenomenon of "Preaching Through Discord."